Endosteal Substitution With an Intramedullary Rod in Fractures of the Femur. (February 2018) - Spitler, Clay A.; Bergin, Patrick F.; Russell, George V.; Graves, Matthew L.
Abstract : Background: Morbid obesity and segmental fracture/bone loss are challenging problems in the treatment of fractures and nonunions of the distal femur. The use of an intramedullary rod as an endosteal substitute for a deficient medial cortex along with a lateral locked plate is 1-tool to combat these problems. This article describes the technique used and its results at a single Level 1 trauma center. Methods: Retrospective chart and radiographic review of all patients treated for acute fractures and nonunions of the distal femur using endosteal substitution with an intramedullary nail and a lateral locked plate. Fixation construct was determined at the surgeon's discretion and was strongly influenced by bone loss and patient body habitus. Results: Seven of 8 acute fractures and 8 of 8 nonunions healed without an unplanned reoperation. There were no cases of secondary displacement after fixation, and only 1 unplanned reoperation in the study group. Conclusion: Endosteal substitution with an intramedullary rod and the use of a lateral locked plate provides the stability needed to allow bone healing under prolonged or supraphysiologic loads seen in morbid obesity or segmental bone loss. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.